On the Experimental Determination of Poisson’s Ratio for Intact Rocks and Its Variation as Deformation Develops - Lu Dong; Hongfa Xu; Pengxian Fan; Zhichou Wu (Advances in Civil Engineering)
Poisson’s ratio is of crucial importance for the theoretical and numerical analysis of rock engineering. It is an elastic parameter of the material and the ratio of the absolute value of lateral strain and axial strain when the material is under uniaxial tension or compression. However, it was rarely investigated compared with deformation modulus and strength. Rock materials are different from metal materials. The pure elastic deformation stage is usually very short or nonexistent in the process of uniaxial tension or compression. In this paper, in order to explore the behavior of Poisson’s ratio, uniaxial compression tests according to The International Society for Rock Mechanics and Rock Engineering are performed on standard specimens of granite, marble, red sandstone, carbonate rock, coral concrete, etc. According to the results, Poisson’s ratio, both the secant Poisson’s ratio and tangent Poisson’s ratio, increase with the externally applied stress. Therefore, regarding it as an elastic constant is worthy of a second thought. If the midpoint of the stress interval is fixed in the 50% of uniaxial compressive strength, the average Poisson’s ratio is almost impervious to the varying span of the stress interval. In addition, the average Poisson’s ratio is immune to the nonlinear deformation in the early loading stage. Thus, the average Poisson’s ratio is a better index than the secant Poisson’s ratio in describing the relationship between axial and lateral strains of hard rocks. The determination of Poisson’s ratio of soft rocks needs further investigation because Poisson’s ratio tends to exceed the theoretical limit in relatively low stress levels. The proposed viewpoint provides a deeper insight into the testing, determining, and using of Poisson’s ratio.